Yoga Practice As a Coping Strategy for Older Adults in Assisted Living Facilities: A Qualitative Content Analysis - Em V. Adams; Brandi M. Crowe; Marieke Van Puymbroeck; Arlene A. Schmid (Mary Ann Liebert, 2022)
Introduction: Living in an assisted living facility (ALF) can be stressful for some residents. Hatha yoga has been demonstrated to facilitate coping among the general population, but this has not been explored with residents of ALFs. The purpose of this study was to explore participants' proactive use of yoga during and after a yoga intervention in ALFs. Methods: An 8-week yoga intervention was implemented across four different ALFs with 15 participants (female?=?13, male?=?2). Attendance and engagement at twice-weekly yoga groups were tracked, and participants' yoga practice use outside of the intervention was tracked through weekly open-ended questions and explored in postintervention semistructured interviews. A conventional content analysis was employed to evaluate residents' perceived use of yoga. Results: Results yielded an overall theme of proactive coping with three subthemes related to the use of yoga: relaxing, energizing, and connecting. Discussion: This implies that yoga may be an effective strategy for some individuals to cope with stress, and promote a higher quality of life within an ALF community. Clinicians, staff, and administrators of ALFs may consider how they can support independent personal yoga practice as well as group yoga practice among residents.